(untitled) (European Journal of Marketing and Economics, 2022)
The article is about economic problems, economic growth, and development in Georgia in conditions of universal globalization in the world. In the modern conditions its hard to find national economy, which isnt included in the system of the world economy. Globalization-integration is an irreversible tendency in the world economic development, which is characterized by high growth quality of relationships between national economics. Economic development is a necessary condition for solving many challenges facing Georgia.